Modulation of Interhemispheric Functional Coordination in Breast Cancer Patients Receiving Chemotherapy - Tao, Longxiang; Wang, Lu; Chen, Xingui; Liu, Fujun; Ruan, Feiyan; Zhang, Jingjie; Shen, Li; Yu, Yongqiang (Frontiers in Psychology, 2020)
Objectives: Chemotherapy induces cognitive impairments including memory impairment attention deficit and executive dysfunction in patients with breast cancer (BC) during or after chemotherapy. Previous studies identified brain structural and functional changes in BC patients receiving chemotherapy; however, there are no studies assessing functional connectivity (FC) between homotopic brain regions in BC patients using a voxel-mirrored homotopic connectivity (VMHC) method. In the present study, we explored cognitive function and whole brain homotopic FC in BC patients receiving chemotherapy compared with healthy controls using the VMHC method. Methods: The present cross-sectional study included 35 premenopausal women with breast cancer who received chemotherapy, as well as 32 age- and sex-matched healthy controls (HC). All subjects underwent resting-state functional magnetic resonance imaging, which measured homotopic brain FC, and cognitive neuropsychological assessments evaluating attention, memory, and executive function domains. Results: The BC group had lower VMHC than the HC group in the cingulated posterior, insular and postcentral regions. No region exhibited higher VMHC in the BC group than in HC group. Correlation analysis in the BC group indicated that VMHC values in the cingulated posterior were significantly correlated with executive function tests, and that the VMHC values in the insular were significantly correlated with memory tests. Conclusion: The present study showed that VMHC decreased in different brain regions including cingulated posterior, insular and postcentral regions. A significant correlation was observed between the VMHC values in the brain regions and neuropsychological tests. These results suggested that changes in VMHC values in different brain regions may underlie cognitive changes in BC patients receiving chemotherapy.